2019
DOI: 10.31704/ijocis.2019.009
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of the teaching readiness level of prospective teachers in terms of curriculum literacy

Abstract: Curriculum literacy is in the forefront to increase the professional competence of teachers. Based on this, the study focuses on the extent of pre-service teachers’ curriculum literacy level on their teacher readiness. The study is designed in a predictive correlation model. Thus, it is focused on whether pre-service teachers’ curriculum literacy is a meaningful predictor of the level of readiness for the teaching profession or not. 708 pre-service teachers participated in the research who studies in Primary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
6
0
6
Order By: Relevance
“…The findings of the research show that geography teachers' perceptions of curriculum literacy level are high. This result is similar to the studies of Aygün (2019), Güleş (2022), Bolat (2017), Aslan & Gürlen (2019), Sural &Dedebali (2018, Erdem & Eğmir (2018), Çetinkaya & Tabak (2019), Keskin (2020) and Yılmaz (2021). When the effect of the participants' participation in any curriculum development study on their perceptions of the level of curriculum literacy was examined, it was determined that there was a significant difference in favor of those who received training throughout the scale.…”
Section: Summary Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the research show that geography teachers' perceptions of curriculum literacy level are high. This result is similar to the studies of Aygün (2019), Güleş (2022), Bolat (2017), Aslan & Gürlen (2019), Sural &Dedebali (2018, Erdem & Eğmir (2018), Çetinkaya & Tabak (2019), Keskin (2020) and Yılmaz (2021). When the effect of the participants' participation in any curriculum development study on their perceptions of the level of curriculum literacy was examined, it was determined that there was a significant difference in favor of those who received training throughout the scale.…”
Section: Summary Introductionsupporting
confidence: 91%
“…Benzer biçimde ölçeğin programı tanıma ve programa hayat verme alt boyutlarında da 21 yıl ve üzeri kıdeme sahip olanlarla lehine anlamlı fark olduğu belirlenmiştir. Bu durumAygün (2019) tarafından yapılan çalışmadaki dördüncü sınıf öğrencilerinin hem eğitim programı okuryazarlığı düzeylerinin hem de öğretmenlik mesleğine hazır bulunuşluk düzeylerinin daha yüksek olduğu bulgusu ile çelişmektedir Güleş (2022). çalışmasında ilkokul ve ortaokul öğretmenlerinin öğretim programına bağlılıklarının meslekte görev aldıkları sürelere göre farklılaşma göstermediği belirtilmiştir.…”
unclassified
“…When other research findings in the literature regarding the curriculum literacy levels of teacher candidates in various fields in terms of gender variable (Aslan, 2018;Boncuk, 2021;Demir & Toraman, 2021;Dilek, 2020;Erdem & Eğmir, 2018;Keskin, 2020;Sarıca, 2021;Şinego & Çakmak, 2021;Tunçer & Şahin, 2019) were examined, parallel findings were observed to be obtained with our study finding. However, the curriculum literacy levels of teacher and/or teacher candidates were found to significantly change in favour of men or women according to the gender variable in some studies (Aygün, 2019;Erdamar, 2020;Erdem & Eğmir, 2018;Gömleksiz & Erdem, 2018;Kahramanoğlu, 2019;Ustabulut, 2021). At this point, it can be uttered that gender is not a significant predictor of curriculum literacy level of teacher candidates considering the general literature.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is necessary to know how teacher candidates, who will play a key role in education, understand the curriculum and what their knowledge, skills and knowledge are for the implementation of the program. When the literature is examined, it is observed that current researches are performed on the curriculum literacy of teacher candidates in various branches (Aygün, 2019;Çetinkaya & Tabak, 2019;Dilek, 2020;Erdem & Eğmir, 2018;Gömleksiz & Erdem, 2018;Gülpek, 2020;Kana et al, 2018;Tunçer & Şahin, 2019;Ustabulut, 2021). Among these studies, only Gülpek's (2020) tion teacher candidates, it has been analysed whether gender, the type of high school they graduated from, and the type of faculty and college to which the program they studied is affiliated have a significant predictive impact on the curriculum literacy levels of physical education teacher candidates.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this complex web of factors, PSTs' preparedness to teach has been examined from different perspectives including curriculum knowledge (Aygün, 2019); teaching knowledge and skills, such as classroom management and knowledge of assessment or teaching multicultural students (İnceçay & Keşli Dollar, 2012;Magogwe & Ketsitlile, 2015;Xu & He, 2019); integration of technology into teaching (Batane & Ngwako, 2017;Gill et al, 2015); teaching practice in TP (Brown et al, 2015(Brown et al, , 2021; strengths and weaknesses of it (Celen & Akcan, 2017); or type of program being certified (Kee, 2011). In short, various lenses, contexts, and constructs have been brought together to interpret preparedness to teach.…”
Section: Theoretical Backgroundmentioning
confidence: 99%